Multilayer-laminated composite cross-sectional fiber

The multi-layer laminated composite cross-section fiber, with its optimized distribution of inorganic particles and moisture-absorbing polymers, achieves high transparency, UV protection, and mechanical strength, addressing the challenges faced by previous composite fibers.

JP2025059328APending Publication Date: 2025-04-10TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023169367
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing composite fibers struggle to achieve high concentrations of inorganic particles while maintaining mechanical strength and transparency, which is necessary for effective UV protection, heat shielding, and moisture absorption.

Method used

A multi-layer laminated composite cross-section fiber is developed, featuring a structure with three or more types of polymer components, including a moisture-absorbing polymer like PEG copolymer, and inorganic particles distributed across layers to achieve a balanced area ratio, thereby enhancing transparency, UV protection, and mechanical properties.

Benefits of technology

The solution provides a fiber with excellent sweat stain suppression, high transparency, UV protection, heat shielding, and moisture absorption, while maintaining strong mechanical properties and processability, thus addressing the limitations of previous technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059328000001_ABST
    Figure 2025059328000001_ABST
Patent Text Reader

Abstract

To provide a multilayer-laminated composite cross-sectional fiber having high anti-see-through property, UV-cut property, thermal insulation property, sweat stain suppression, hygroscopic property, and excellent mechanical characteristics and having raw yarn strength satisfying process-passing property and high-degree properties.SOLUTION: A multilayer-laminated composite cross-sectional fiber has, in a fiber cross section vertical to a fiber axis direction, a multilayer structure comprising a laminate of 3 to 15 layers of polymeric components of three or more kinds similar to a fiber surface, contains inorganic particles in an amount of 5 mass% to 40 mass% relative to the entire fiber, and has a ΔMR of 2.0% or more and 10.0% or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite cross-section fiber containing three or more polymers and having multiple layers laminated in conformity with the fiber surface. [Background technology]

[0002] Synthetic fibers made of polyester and polyamide have excellent mechanical properties and dimensional stability, and are therefore widely used in clothing and industrial applications. However, as people's lives have become more diverse and people seek more comfortable lives, there is a demand for fibers with advanced functions not found in conventional synthetic fibers for many applications, including clothing. In particular, with the recent increase in global warming, there is a demand for spring and summer clothing that has excellent UV protection and heat insulation properties against sunlight, and that is thin but opaque.

[0003] In particular, polyester fibers are used in a wide range of applications because they are relatively inexpensive and have an excellent dry feel, but because they have poor moisture absorption properties, they have problems to be solved in terms of comfort when worn, such as stuffiness during high humidity in summer and static electricity during low humidity in winter.

[0004] Methods for imparting moisture absorbency to polyester fibers include copolymerization of a hydrophilic compound with polyester and addition of a hydrophilic processed product. For example, Patent Document 1 describes an islands-in-sea type composite fiber in which island components are polymers having moisture absorbency.

[0005] Patent Document 2 describes a core-sheath type composite fiber having an area ratio of core component:sheath component in the range of (25:75) to (60:40) in the fiber cross section, in which a hygroscopic polymer is disposed in the core component, the core component being a thermoplastic polymer having a hygroscopic rate of 8 to 12% in an atmosphere of 20°C x 90% RH, and the sheath component being a polyester containing 1.0 to 10.0 wt% of ultraviolet shielding particles, based on the weight of the polymer constituting the sheath component, and the surface of the core-sheath type composite fiber is roughened by alkali reduction. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2018 / 012318 [Patent Document 2] Japanese Patent Application Publication No. 9-256224 Summary of the Invention [Problem to be solved by the invention]

[0007] The islands-in-sea type composite fiber described in Patent Document 1 uses a hygroscopic polymer for the island component, and by optimizing the thickness of the sea component of the outermost layer, it is possible to suppress cracking of the sea component caused by volumetric swelling of the hygroscopic polymer of the island component and elution of the hygroscopic polymer, and has excellent hygroscopicity even after hot water treatment such as dyeing. However, when inorganic particles are contained at a high concentration, a layer of inorganic particles is arranged in the outermost layer, so sufficient strength cannot be obtained and mechanical properties, processability, and high-order quality are deteriorated. Therefore, it is not possible to increase the concentration of inorganic particles, and high anti-see-through properties, UV protection properties, and heat shielding properties cannot be achieved.

[0008] Patent Document 2 discloses a composite fiber in which a thermoplastic polymer having a moisture absorption rate of 8-12% in an atmosphere of 20°C x 90% RH is contained in the core component, and 1.0-10.0% by weight of ultraviolet shielding particles based on the weight of the polymer constituting the sheath component is contained in the sheath component, and although the fiber has moisture absorption and a dry touch, the content of the ultraviolet shielding particles is low, and the high anti-transparency and UV protection required in recent years cannot be achieved. In addition, when the ultraviolet shielding particles are contained at a high concentration, the polymer containing the ultraviolet shielding particles is disposed in the sheath component, so sufficient strength cannot be obtained, and excellent mechanical properties, processability, and high quality cannot be obtained.

[0009] The present invention solves the conventional problems by arranging a layer containing a high concentration of inorganic particles inside the outermost layer, and then arranging a moisture-absorbing polymer further inside, and balancing the area ratios of each layer, thereby providing a multi-layer laminated composite cross-section fiber that has high anti-transparency properties, UV protection properties, heat insulation properties, sweat stain prevention, moisture absorption properties, excellent mechanical properties, and raw yarn strength that satisfies processability and high quality. [Means for solving the problem]

[0010] The present invention is achieved by the following means: (1) A multilayer laminated composite cross-section fiber having a multilayer structure in which three or more types of polymer components are laminated in 3 to 15 layers similar to the fiber surface in the fiber cross-section perpendicular to the fiber axis direction, the fiber contains 5% by mass to 40% by mass of inorganic particles with respect to the entire fiber, and has a ΔMR of 2.0% or more and 10.0% or less. (2) The multi-layer laminated composite cross section fiber according to (1) above, wherein one of the three or more polymer components is a moisture-absorbing polymer, and the moisture-absorbing polymer is a PEG copolymer. (3) The multi-layer laminated composite cross-section fiber according to (1) above, wherein the three or more polymer components are all polyester and have a strength of 2.0 cN / dtex or more. (4) The multi-layer laminated composite cross-section fiber according to (1), wherein at least one layer closer to the center of the fiber than the outermost layer of the multi-layered fiber surface contains 30% to 70% by mass of inorganic particles, and the total area ratio of the layers containing the inorganic particles is 10% to 40%. Effect of the Invention

[0011] INDUSTRIAL APPLICABILITY The multi-layer laminated composite cross section fiber of the present invention can provide a comfortable material that is optimal for clothing applications and has excellent sweat stain prevention, high opacity, UV protection, heat insulation, and moisture absorption properties. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic diagram of a composite spinneret for explaining the production of the multi-layer laminated composite cross-section fiber of the present invention. [Diagram 2]FIG. 2 is a schematic diagram of a fiber cross section for illustrating the multilayer structure of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, embodiments of the present invention will be described in detail. The laminated multilayer structure in the multi-layer laminated composite cross section fiber of the present invention means a fiber having a multilayer structure from the fiber surface to the fiber center in a fiber cross section perpendicular to the fiber axis direction, and a multilayer structure is formed in which at least three or more types of polymer components are laminated in three or more layers similar to each other on the fiber surface.

[0014] The number of layers in the multi-layer laminated composite cross-section fiber of the present invention is 3 to 15 layers. Although the more layers in the multi-layer structure, the more the anti-see-through property is improved, the effect becomes saturated. If the number of layers exceeds 15 layers, from the viewpoint of spinning, abnormalities in cross-section formability occur, which leads to quality abnormalities. Therefore, from the viewpoints of the objectives of the present invention, such as the anti-see-through property, UV protection property, and heat shielding properties, moisture absorption, and basic fiber properties and quality, 3 to 9 layers are preferable, and 3 to 5 layers are more preferable.

[0015] In the multi-layer laminated composite cross-section fiber of the present invention, the thickness of the outermost layer of the multi-layer structure is preferably 0.40 μm or more. If it is less than 0.40 μm, abnormalities in cross-section formation occur from the viewpoint of spinning, causing quality abnormalities. More preferably, it is 0.40 to 0.85 μm. By setting it in this range, not only is it possible to obtain excellent anti-see-through properties, UV protection properties, and heat shielding properties, but it also exhibits a sweat stain suppression effect. Sweat stains are a phenomenon in which clothing appears darker due to sweat, making it look like a stain. That is, when a fabric gets wet with water, the surface reflected light of sunlight decreases and the transmitted light increases, causing the color to appear darker. Sweat stains are particularly noticeable on light colors that are preferably used in spring and summer clothing, so there is a high consumer demand for spring and summer clothing in which sweat stains are not noticeable.

[0016] In the multi-layer laminated composite cross-section fiber of the present invention, the inorganic particles are contained in an amount of 5% to 40% by mass based on the entire fiber. By setting the amount within this range, excellent shielding performance such as sweat stain inhibition, anti-see-through property, UV protection, and heat shielding is obtained. If the inorganic particle content is more than 40% by mass, the shielding performance such as sweat stain inhibition, anti-see-through property, UV protection, and heat shielding is improved, but the effect is saturated and the basic physical properties of the fiber such as strength are reduced. If the inorganic particle content is less than 5% by mass, the shielding performance such as sweat stain inhibition, anti-see-through property, UV protection, and heat shielding is not obtained. The preferable inorganic particle content is 10% to 30% by mass.

[0017] In the multi-layer laminated composite cross-section fiber of the present invention, a thin layer is arranged on the outermost layer, and a layer having a high effect of absorbing and scattering solar light is arranged inside the outermost layer in at least one layer closer to the center of the fiber than the outermost layer. In at least one layer closer to the center of the fiber than the outermost layer of this multi-layer structure, the content of inorganic particles is preferably 30% by mass to 70% by mass. From the viewpoints of the shielding performance such as anti-see-through properties, UV protection properties, and heat shielding properties, and the prevention of sweat stains, the content is preferably 30% by mass or more, and more preferably 40% by mass or more.

[0018] In the multi-layer laminated composite cross-section fiber of the present invention, the content of inorganic particles in the outermost layer of the multi-layer structure is preferably 0.1% by mass to 3.0% by mass. By making the content of inorganic particles in the outermost layer 0.1% by mass or more, it is possible to reduce friction with the fiber guide and suppress fluffing, which is preferable from the viewpoint of quality in terms of spinning and higher-order processes. More preferably, the content of inorganic particles in the outermost layer is 2.0% by mass or less.

[0019] Sunlight contains visible light, infrared rays, and ultraviolet rays, and it is desirable for spring and summer clothing to have the functionality to block these rays and suppress the rise in temperature inside the clothing (heat shielding). Inorganic particles have the effect of absorbing and scattering these rays, and by kneading them into fibers, it is possible to improve the shielding performance of anti-transparency, UV cut (ultraviolet ray shielding), and heat shielding.

[0020] The inorganic particles contained in the multi-layer laminated composite cross section fiber of the present invention are preferably inorganic particles having a material refractive index of 2.0 or more. The higher the material refractive index of the inorganic particles, the better the effect of absorbing and scattering solar light. Preferred inorganic particles are titanium oxide (rutile type: 2.72), titanium oxide (anatase type: 2.52), zirconium oxide (2.20), and zinc oxide (2.01). The numbers in parentheses are the material refractive indexes.

[0021] Among these, titanium dioxide is more preferred in terms of its sunlight shielding properties and ease of handling. The sunlight shielding properties refer to UV cut properties that absorb and shield ultraviolet rays that are harmful to the skin, heat shielding properties that efficiently reflect sunlight in the visible and near infrared regions, suppressing the absorption of solar energy and suppressing temperature increases inside clothing, and opacity that makes it difficult for light to pass through.

[0022] In the multi-layer laminated composite cross-section fiber of the present invention, the content of inorganic particles in the outermost layer is preferably 0.1% by mass to 3.0% by mass. In addition, it is preferable to arrange a layer containing inorganic particles at a high concentration closer to the fiber center than the outermost layer. If a layer containing inorganic particles at a high concentration is arranged in the outermost layer, the strength decreases and the mechanical properties and processability deteriorate. In addition, it is preferable to arrange a layer containing a hygroscopic polymer in a layer closer to the fiber center than the layer containing inorganic particles at a high concentration. In general, hygroscopic polymers tend to swell in volume by hot water treatment such as dyeing, and also tend to dissolve in hot water. In fibers in which a hygroscopic polymer is arranged alone or in the outermost layer, the hygroscopic polymer dissolves by hot water treatment, and the dissolved part causes dye spots and fluff, resulting in a decrease in quality. In addition, in polymers copolymerized with hydrophilic copolymer components such as PEG copolymers, the hydrophilic copolymer components dissolve by hot water treatment, resulting in a decrease in hygroscopicity. In addition, polymers copolymerized with hydrophilic copolymerization components generally have a high yellowness, which impairs the color of the fiber when used alone or in the outermost layer. By placing a thin layer in the outermost layer, placing a layer with high solar absorption and diffuse reflection effect in the layer closer to the fiber center than the outermost layer, and further placing a layer containing a moisture-absorbing polymer in the layer closer to the fiber center, the volumetric swelling of the moisture-absorbing polymer is suppressed, and performance that satisfies both the shielding performance of anti-transparency, UV protection, and heat shielding, as well as water absorption, can be obtained. Furthermore, since the color of the moisture-absorbing polymer can be covered, it is expected to be used in applications where the base color is white, such as woven and knitted clothing fabrics, especially business shirts.

[0023] In the multi-layer laminated composite cross-section fiber of the present invention, the total area ratio of the layers containing inorganic particles at a high concentration is 10 to 40%, and more preferably 20 to 30%. By setting it in this range, excellent shielding performance such as anti-see-through property, UV protection property, and heat shielding property is obtained. If the total area ratio of the layers containing inorganic particles is 10% or less, the content of inorganic particles contained in the entire fiber is reduced, and the effects of the shielding performance such as anti-see-through property, UV protection property, and heat shielding property are not exhibited. If the total area ratio of the layers containing inorganic particles is 40% or more, a strength that satisfies the processability cannot be obtained.

[0024] The multi-layer laminated composite cross-section fiber of the present invention has a hygroscopic polymer. In the present invention, the hygroscopic polymer is a polymer having a moisture absorption rate difference (ΔMR) of 2.0 to 30.0%. The moisture absorption rate difference (ΔMR) in the present invention refers to a value measured by the method described in the Examples. If the ΔMR of the hygroscopic polymer is 2.0% or more, a multi-layer laminated composite cross-section having excellent moisture absorption properties can be obtained. The ΔMR of the hygroscopic polymer is more preferably 2.5% or more, even more preferably 3.0% or more, and particularly preferably 4.0% or more. On the other hand, if the ΔMR of the hygroscopic polymer is 10.0% or less, even in a multi-layer laminated composite cross-section in which three or more types of polymer components are laminated in parallel in three layers, excellent mechanical properties, processability, and strength with good high-order quality can be obtained.

[0025] In the multi-layer laminated composite cross section fiber of the present invention, it is preferable that the layer containing inorganic particles at a high concentration and the layer containing a hygroscopic polymer are separated. By containing inorganic particles and hygroscopic polymer at a high concentration in each layer, it is possible to obtain the intended high anti-see-through properties, UV protection properties, heat shielding properties, and hygroscopic properties.

[0026] In the multi-layer laminated composite cross-section fiber of the present invention, the total area ratio of the layers containing the hygroscopic polymer is 10 to 40%, more preferably 15 to 30%. By setting it in this range, excellent hygroscopicity is obtained. If the total area ratio of the layers containing the hygroscopic polymer is 10% or less, the content of the hygroscopic polymer contained in the entire fiber is reduced, and water absorption is not exhibited. If the total area ratio of the layers containing the hygroscopic polymer is 30% or more, strength sufficient for processability cannot be obtained.

[0027] In the multi-layer laminated composite cross-section fiber of the present invention, the total area ratio of the layer containing inorganic particles at a high concentration and the layer containing a hygroscopic polymer is preferably 20 to 55%. By setting it in this range, the multi-layer laminated composite cross-section fiber in which three or more types of polymers are laminated can obtain strength with good processability.

[0028] Specific examples of polyethers that are copolymerization components of the hygroscopic polymer include homopolymers such as polyethylene glycol, polypropylene glycol, and polybutylene glycol, and copolymers such as polyethylene glycol-polypropylene glycol copolymer and polyethylene glycol-polybutylene glycol copolymer. These are preferred because they have good handleability during production and use, and polyethylene glycol is particularly preferred because of its excellent hygroscopicity.

[0029] The copolymerization rate of the PEG copolymer is preferably 10 to 60% by weight. If the copolymerization rate is 10% by weight or more, the hygroscopicity of the hygroscopic polymer is high, and when the total area ratio of the layers containing the hygroscopic polymer is taken, a multi-layer laminated composite cross-section fiber having excellent hygroscopicity can be obtained. The copolymerization rate is more preferably 20% by weight or more, and even more preferably 30% by weight or more. On the other hand, if the copolymerization rate is 60% by weight or less, the amount of unreacted polyethylene glycol can be reduced, and the elution of the hygroscopic polymer of the island component into hot water during hot water treatment such as dyeing can be suppressed, and the hygroscopicity can be maintained even after the hot water treatment, which is preferable. The copolymerization rate of the polyether is more preferably 55% by weight or less, and even more preferably 50% by weight or less.

[0030] The strength of the multifilament made of the multilayer laminated composite cross section fiber of the present invention is preferably 2.0 cN / dtex or more for drawn yarn (DT), 1.3 cN / dtex or more for semi-drawn yarn (POY), and 2.0 cN / dtex or more for false twist textured yarn (DTY). By being in such a range, a multilayer laminated composite cross section fiber having excellent mechanical properties and processability can be obtained.

[0031] The single yarn fineness of the multi-layer laminated composite cross-section fiber of the present invention is 0.7 dtex to 3.5 dtex. For clothing applications, importance is attached to texture. To obtain the soft texture required for clothing applications, the single yarn fineness is 3.5 dtex or less. For innerwear that comes into direct contact with the skin, shirt fabrics, and down linings, the preferred single yarn fineness is 2.0 dtex or less. The smaller the single yarn fineness, the softer the texture, but if the single yarn fineness is less than 0.7 dtex, it becomes difficult to form the cross section of the layer containing inorganic particles.

[0032] The multi-layer laminated cross section fiber of the present invention is preferably a long fiber, constituting a multifilament (including textured yarn). The number of filaments preferably used for clothing is 12 to 144, and the total fineness is 10 dtex to 200 dtex. The method for producing the multi-layer laminated composite cross-section fiber of the present invention will be described below.

[0033] The three or more polymer components constituting the multi-layer laminated composite cross-section fiber of the present invention are not particularly limited as long as they are fiber-forming thermoplastic polymers. In the multi-layer structure of the fiber, it is preferable to use the same type of polymer from the viewpoints of preventing peeling between layers, forming a composite cross-section, and spinnability. In the combination of the same type of polymer, different compositions, such as different viscosities and different contents of inorganic particles, may be used. From the viewpoint of processability, it is preferable that the polymer types are all polyester or all polyamide. In addition, since sweat stains are a phenomenon that occurs when wet with water, it is preferable that the polymer types have an official moisture regain of 5% or less, and polyester is preferable. For clothing applications, polyester is preferable because it is inexpensive and has excellent mechanical properties and dry feeling.

[0034] Furthermore, as environmental issues have come to the forefront of attention, the use of plant-derived biopolymers and recycled polymers in the present invention is also preferable from the viewpoint of reducing the environmental impact, and the polymers used in the present invention described above can be recycled polymers that have been recycled by any of the methods of chemical recycling, material recycling, and thermal recycling.

[0035] The polyester is preferably polyethylene terephthalate (PET) in which 80 mol% or more of the repeating units are ethylene terephthalate, polybutylene terephthalate (PBT) in which 80 mol% or more of the repeating units are butylene terephthalate, or polytrimethylene terephthalate (PTT) in which 80 mol% or more of the repeating units are trimethylene terephthalate. In addition, aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, naphthalene 2,6-dicarboxylic acid, phthalic acid, and 5-sodium sulfoisophthalic acid, and aliphatic dicarboxylic acids such as adipic acid and sebacic acid may be copolymerized as a third component to an extent that the fiber formability of the homopolymer is not impaired.

[0036] In the melt spinning of the multi-layer laminated composite cross-section fiber of the present invention, the higher the concentration of inorganic particles in the fiber-forming thermoplastic polymer, the stronger the intermolecular interactions of the inorganic particles, so that the fluidity of the polymer decreases when melted, melt fracture is likely to occur, and the formability of the composite cross section is likely to become unstable. Therefore, in order to arrange the polymer component containing inorganic particles at a high concentration in the cross-sectional form shown in Figure 2, it is preferable to appropriately adjust the polymerization degree of the base polymer containing inorganic particles at a high concentration.

[0037] In the case of polyester, the intrinsic viscosity (hereinafter referred to as IV) is preferably 0.51 to 0.8. When the IV is 0.51 or more, the degree of polymerization is not too low, and the composite fiber has sufficient strength to withstand practical use, which is preferable. On the other hand, when the IV is 0.8 or less, melt fracture does not occur, a uniform multi-layer laminated composite cross section fiber is obtained, and the strength does not decrease, which is preferable.

[0038] In the case of polyamide, the sulfuric acid relative viscosity (hereinafter referred to as ηr) is preferably 2.0 to 3.0. When ηr is 2.0 or more, the degree of polymerization is not too low, and the composite fiber has sufficient strength to withstand practical use, which is preferable. On the other hand, when ηr is 3.0 or less, melt fracture does not occur, a uniform multi-layer laminated composite cross section fiber is obtained, and the strength does not decrease, which is preferable.

[0039] In the multi-layer laminated composite cross-section fiber of the present invention, a thin layer is arranged on the outermost layer, and a polymer layer containing inorganic particles at a high concentration is arranged on at least one layer closer to the fiber center than the outermost layer. The inorganic particle content of the polymer layer containing inorganic particles at a high concentration is preferably 30% by mass to 70% by mass, and the inorganic particle content of the outermost layer is preferably 0.1% by mass to 3.0% by mass. The inorganic particle content of the outermost layer is preferably 3.0% by mass or less, and when the difference in the inorganic particle content between adjacent layers is large, a large difference occurs in the polymer fluidity during melting, so in order to uniformly form a thin layer on the outermost layer, it is preferable that the degree of polymerization of the polymer component of the outermost layer is higher than that of the polymer component of the adjacent layer.

[0040] The multi-layer laminated composite cross-section fiber of the present invention is produced by a composite spinning machine capable of melting three or more kinds of polymer components separately. When melting the fiber-forming thermoplastic polymer, the pressure melter method or the extruder method can be mentioned, but is not particularly limited. The melting temperature may be appropriately determined in consideration of the melting point of the fiber-forming thermoplastic polymer, but the preferred melting temperature is a temperature 20°C to 60°C higher than the melting point at which the polymer components are melted separately. The spinning temperature is the same as the melting temperature, and may be appropriately determined in consideration of the melting point of the fiber-forming thermoplastic polymer. The spinning temperature here is the so-called heat-retaining temperature (spin block temperature) at which the polymer piping, metering pump, spinneret, etc. are kept warm.

[0041] The separately melted fiber-forming thermoplastic polymers are each metered and fed to a composite spinneret, where three or more types of fiber-forming thermoplastic polymers join together to form a multi-layered composite cross section, which is then extruded from the nozzle of the spinneret.

[0042] As the composite spinneret used for the multi-layer laminated composite cross-section fiber of the present invention, it is preferable to use the composite spinneret described in JP 2011-208313 A. The composite spinneret shown in Fig. 1 is assembled in a spinning pack in a laminated state of three major components, namely, from the top, a metering plate (1), a distribution plate (2) and a discharge plate (3), and is used for spinning. Incidentally, Fig. 1 shows an example in which three types of polymers, namely, polymer A, polymer B and polymer C, are used, but if necessary, four or more types of polymers may be used for spinning. With conventional composite spinnerets, it is difficult to composite three or more types of polymers, and it is preferable to use a composite spinneret utilizing a fine flow path as exemplified in Fig. 1.

[0043] The discharged yarn is cooled and solidified by a yarn cooling device, and then a spinning oil is applied by an oiling device. The yarn is wound around a drum and then drawn in a two-step process, or the yarn is drawn without being wound up in a one-step process. Alternatively, the yarn is semi-drawn by an appropriate spinning draft without being wound up. These production methods will be described in detail.

[0044] In producing the semi-drawn yarn, it is preferable to take up the yarn by a suitable spinning draft, and the spinning speed is preferably 3000 to 5000 m / min.

[0045] In the case of drawn yarn, the direct spinning and drawing method, which is a one-step method, is preferred in consideration of the ease of fiber structure formation, i.e., tension control from spinning to winding. The spinning speed is preferably 500 m / min to 6000 m / min. For drawing, it is preferable to set the preheating temperature appropriately, using the temperature at which the polymer can be softened, such as the glass transition temperature, as a guide. The upper limit of the preheating temperature is preferably a temperature at which yarn path disturbance does not occur due to spontaneous elongation of the fiber during the preheating process. For example, in the case of PET, which has a glass transition temperature of around 70°C, the preheating temperature is usually set at about 80°C to 95°C. In addition, in the case of polyamide, whose glass transition temperature drops to room temperature due to moisture absorption, the preheating temperature setting is unnecessary or is set at 25°C to 70°C.

[0046] The multi-layer laminated fiber with composite cross section of the present invention may be subjected to known yarn processing such as false twist processing and taslan processing in order to impart further functionality.

[0047] The false twisting can be achieved by a conventionally known false twisting technique, and preferably, false twisting is performed using a stretch-friction false twisting device. Examples are as follows. For example, a semi-drawn yarn supplied to a stretch-friction false twisting device is sent to a supply roller via a desired yarn guide or fluid treatment device. The yarn is then guided to a stretching roller through a heated heater, a cooling plate, and a twisting body that performs stretch-friction false twisting, and wound up as a false twisted yarn. As for the stretch-friction false twisting, the yarn may be subjected to friction false twisting after being stretched using a hot pin or hot plate before the supply roller of the stretch-friction false twisting device, or may be subjected to friction false twisting while being stretched between the supply roller and the stretching roller.

[0048] The twisting body is not limited to a pin type, a friction type, a belt nip type, etc. When it is desired to strengthen the crimp, it is preferable to use the pin type, and when it is desired to increase the processing speed and reduce the production cost, it is preferable to use the friction type or the belt nip type.

[0049] The heating method of the heater includes, but is not limited to, high-temperature contact heaters and high-temperature non-contact heaters, but in order to obtain high shrink performance, it is necessary to apply heat firmly to the yarn with a high-temperature contact heater to rearrange the molecules in the fiber and relieve the distortion. Therefore, a high-temperature contact heater is preferable, and the processing temperature (heater setting temperature with a contact type hot plate) is preferably 170°C to 200°C.

[0050] The form of the fiber structure made of the multi-layer laminated composite cross section fiber of the present invention is not particularly limited, and it can be made into woven fabric, knitted fabric, pile fabric, nonwoven fabric, spun yarn, wadding, etc. according to known methods. EXAMPLES

[0051] The present invention will now be described in more detail with reference to examples, in which the methods for measuring the properties are as follows.

[0052] (1) Viscosity A. Intrinsic viscosity (IV) 0.8 g of a polyester chip sample was dissolved in 10 mL of o-chlorophenol with a purity of 98% or higher at 25° C., and the relative viscosity ηr was determined using an Ostwald viscometer at 25° C. according to the following formula. Using this relative viscosity ηr, the intrinsic viscosity (IV) was calculated according to the following formula. ηr=η / η0=(t×d) / (t0×d0) Intrinsic viscosity (IV)=0.0242ηr+0.2634 Here, η is the viscosity of the polymer solution, and η0 is the viscosity of o-chlorophenol. t: time the solution falls (seconds), d: density of the solution (g / cm 3 ), t0: Fall time of o-chlorophenol (sec), d0: Density of o-chlorophenol (g / cm 3 ).

[0053] B. Relative viscosity of sulfuric acid (ηr) 0.25 g of a polyamide chip sample was dissolved in 100 ml of 98% sulfuric acid to give a total volume of 1 g, and the flow time T1 was measured at 25°C using an Ostwald viscometer. Subsequently, the flow time T2 of only the 98% sulfuric acid was measured. The ratio of T1 to T2, i.e., T1 / T2, was determined as the relative viscosity of 98% sulfuric acid.

[0054] (2) Total fineness, single yarn fineness A 100 m skein was prepared using a measuring machine with a frame circumference of 1.0 m, and the fineness was measured according to the following formula. Total fiber size (dtex) = Weight of 100m skein (g) x 100 Single yarn fineness (dtex) = total fineness (dtex) / number of filaments (number of filaments).

[0055] (3) Strength and elongation Measurements were performed according to JIS L1013 (2010, chemical fiber filament yarn test method).

[0056] (4) Composite cross section (number of layers, thickness of outermost layer, area ratio) A. Number of layers The semi-stretched yarn and the stretched yarn were cut at an arbitrary position in the fiber axis direction, and the fiber cross section was observed at a magnification of 6000 times using a KEYENCE microscope to measure the number of layers and the thickness of the outermost layer.

[0057] The number of layers here refers to the total number of layers in the multilayer structure of each polymer component present on a line (line segment AB in Figure 2) drawn from an arbitrary point (A in Figure 2) on the outer circumference of the cross section of one fiber to the center of the fiber (B in Figure 2). It is the average value of measurements taken on five fibers. FIG. 2 shows an example, which is a cross section of a four-layer laminate in which a layer containing a high concentration of inorganic particles is arranged as layer (5) and a layer containing a PEG copolymer is arranged as layer (6).

[0058] The radius of the perfect circle circumscribing the cut surface of the cross section of one fiber was measured as the fiber radius C of the semi-drawn or drawn yarn (line segment AB in Figure 2). Furthermore, the straight line (line segment DB in Figure 2) drawn from an arbitrary point (D in Figure 2) on the circumscribing circle of the polymer layer (5 in Figure 2) located on the central side of the perfect circle circumscribing the cut surface of the fiber cross section to the fiber center (B in Figure 2) was defined as the fiber radius E. B. Outermost layer thickness The thickness of the outermost layer of the semi-drawn or drawn yarn was calculated by (fiber radius C - fiber radius E). Five fibers were measured and the average value was calculated.

[0059] In the case of false twist textured yarn, since the cross-sectional shape changes due to processing, the theoretical fiber radius of a perfect circle was calculated from the fineness of the false twist textured yarn and was taken as the fiber radius Z. The thickness of the outermost layer of the false twist textured yarn is The thickness of the outermost layer of the semi-drawn yarn was calculated as (fiber radius C-fiber radius E) x (fiber radius Z / fiber radius C of the semi-drawn yarn). The specific gravity of polyethylene terephthalate was 1.31, and the specific gravity of polyamide was 1.13.

[0060] C. Area ratio For the polymer layer containing a high concentration of inorganic particles, fiber samples (semi-drawn yarn, drawn yarn, false twist textured yarn) were cut at any position in the fiber axis direction, and the fiber cross section was observed at 6000x magnification using a KEYENCE microscope (VHX-7000). For one fiber, the layer closest to the fiber center and with the darkest shadow (blacker) than the outermost layer was selected, and the cross-sectional area ratio was measured. Five fibers were measured, and the average value was calculated.

[0061] Similarly, for the polymer layer containing the PEG copolymer, a layer with a different shade from the outermost layer and the layer containing the inorganic particles was selected, and the cross-sectional area ratio was measured. Five fibers were measured, and the average value was calculated.

[0062] (5) Inorganic particle content A 7 g fiber sample was melted at 320°C and pressed at a maximum pressure of 100 kN to prepare a measurement sample. The inorganic particle content (g) was quantified using a wavelength dispersive X-ray fluorescence analyzer ZSX PrimusIV manufactured by Rigaku Corporation.

[0063] The content (mass%) of inorganic particles in the entire fiber was calculated as follows. Content of inorganic particles (mass%) = Content of inorganic particles (g) / 7 (sample weight (g)) x 100 The content (mass %) of inorganic particles in one layer was calculated as follows. Fiber samples (semi-drawn yarn, drawn yarn, false twist textured yarn) were cut at any position in the fiber axis direction, and the fiber cross sections were observed at 6000x magnification using a KEYENCE microscope. A layer that was darker (blacker) than the outermost layer was selected closer to the center of the fiber than the outermost layer for one fiber, and the cross-sectional area ratio was measured. Five fibers were measured, and the average value was calculated.

[0064] If one layer is selected Content of inorganic particles in one layer (mass%) = Content of inorganic particles in the entire fiber (mass%) / Cross-sectional area ratio If there are multiple layers selected Inorganic particle content (mass%) of one layer = inorganic particle content (mass%) of the entire fiber / cross-sectional area ratio / number of selected layers.

[0065] (6)PEG copolymerization rate In the present invention, the copolymerization rate of polyethylene glycol copolymerized in the polyester is as follows: It can be calculated by the following procedure. First, about 0.05 g of fiber is placed in the measurement pan of a differential scanning calorimeter (DSC) and heated from room temperature to 300°C to identify the melting peaks originating from the sea component and the island component. From the heat of the melting peak of the sea component, the ratio of the sea component is calculated, and the ratio of the island component is calculated. Furthermore, about 0.08 g of fiber is placed in the measurement tube of a nuclear magnetic resonance spectrometer (NMR) and dissolved by adding 1 g of deuterated 1,1,1,3,3,3-hexafluoro-2-isopropanol (HFIP). This solution is measured by 1H-NMR, and the copolymerization amount of polyethylene glycol copolymerized in the polyester composition can be calculated by using the ratio of the island component calculated from the DSC measurement. In the present invention, when the polyester copolymerized with polyethylene glycol is a polymer or copolymer obtained by a condensation reaction of a dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative as main components, it can be produced by subjecting a dicarboxylic acid or its ester-forming derivative and a diol or its ester-forming derivative to an esterification reaction or an ester exchange reaction, followed by a polycondensation reaction.

[0066] (7) Anti-see-through A tubular knitted fabric was made, and a 1cm x 5cm black backing was attached to a white board. The appearance of the black color was visually judged by five examiners on a three-point scale based on the following criteria. The results were calculated by taking the average of each examiner's evaluation scores and rounding off the decimal point, with 3 points being marked as ◎, 2 points being ○, and 1 point being ×. 3 points and 2 points were considered pass. ◎ (3 points): No black is visible at all. ○ (2 points): Black is slightly visible. × (1 point): Black is clearly visible.

[0067] (8) Moisture absorption rate difference (△MR) The tubular knitting fabric prepared as described above was used as a sample, and the moisture content was calculated according to JIS L1096:2010 (Fabric Testing Method for Woven and Knitted Fabrics) 8.10. First, the tubular knitting fabric was dried with hot air at 60°C for 30 minutes, then left for 24 hours in a thermostatic chamber adjusted to a temperature of 20°C and a humidity of 65%RH, and the weight (W1) of the tubular knitting fabric was measured. Then, the tubular knitting fabric was left for 24 hours in a thermostatic chamber adjusted to a temperature of 30°C and a humidity of 90%RH, and the weight (W2) of the tubular knitting fabric was measured. After that, the tubular knitting fabric was dried with hot air at 105°C for 2 hours, and the weight (W3) of the tubular knitting fabric after bone drying was measured. The weights of the tubular knitting pieces, W1 and W3, were used to calculate the moisture absorption rate MR1 (%) when the fabric was left to stand for 24 hours in an atmosphere with a temperature of 20°C and a humidity of 65% from an absolutely dry state using the formula below. The weights of the tubular knitting pieces, W2 and W3, were used to calculate the moisture absorption rate MR2 (%) when the fabric was left to stand for 24 hours in an atmosphere with a temperature of 30°C and a humidity of 90% from an absolutely dry state using the formula below. The difference in moisture absorption rate (△MR) was then calculated using the formula below. MR1(%)={(W1-W3) / W3}×100 MR2(%)={(W2-W3) / W3}×100 Moisture absorption rate difference (△MR) (%) = MR2-MR1 (9) Dryness The tubular knitting products produced as described above were judged by five inspectors on a three-point scale based on the following criteria. The results were calculated by taking the average of the inspectors' evaluation scores and rounding off the decimal point, with an average of 3 points being marked as ◎, 2 points being ○, and 1 point being ×. 3 points and 2 points were considered pass. ◎ (3 points): Not slimy or sticky at all, with an extremely dry feel. ◯ (2 points): Almost no slime or stickiness, with an excellent dry feel. × (1 point): Extremely slimy and sticky, with very poor dry feeling.

[0068] (10) Process passability Regarding the spinning operability, the number of yarn breakages relative to the amount of spinning was checked and judged on a three-level scale based on the following criteria. ◎: Yarn breakage 3 times / t or less. Good: Yarn breakage 3 to 5 times / t. ×: Yarn breakage 5 times / t or more.

[0069] Example 1 A polyester made of polyethylene terephthalate with an intrinsic viscosity of 0.56 and containing 50% by mass of rutile-type titanium oxide is used as polymer component 1. A polyethylene terephthalate copolymerized with 50% by weight of polyethylene glycol (PEG6000S manufactured by Sanyo Chemical Industries) is used as polymer component 2. A polyethylene terephthalate with an intrinsic viscosity of 0.64 and containing 0.3% by mass of titanium oxide is used as polymer component 3.

[0070] A three-component composite spinning machine is used, and the extrusion rate of each component polymer is adjusted using individual extruders, polymer piping, and metering pumps. The outermost layer is made of polymer component 3, the two middle layers are made of polymer component 1, the three middle layers are made of polymer component 3, and the fourth middle layer is made of polymer component 2. A concentric four-layer laminated composite cross section as shown in Figure 2 is extruded using a composite spinneret that utilizes fine flow paths as shown in Figure 1 so that the cross-sectional area ratios of each are polymer component 1: 24%, polymer component 2: 20%, and polymer component 3: 56%.

[0071] The yarn discharged from the composite spinneret was cooled and solidified by a yarn cooling device, and then spinning oil was applied to it by an oiling device. The yarn was then taken up at a take-up roller speed (spinning speed) of 3000 m / min to obtain a semi-oriented yarn (POY) of 140 dtex-72 filaments.

[0072] The obtained POY was drawn and false-twisted (friction processed) simultaneously using a draw-friction false-twist processing device under conditions of a yarn speed of 450 m / min, a draw ratio of 1.7 times, and a heat treatment of 170°C (set temperature of a contact-type hot plate heater), to obtain a false-twisted yarn (DTY) of 84 dtex-72 filaments (single yarn fineness 1.2 dtex) and a strength of 2.5 cN / dtex.

[0073] The thickness of the outermost layer of the DTY was 0.58 μm. The content of inorganic particles in the fiber was 12% by mass. The content of PEG copolymer in the fiber was 10% by mass. The obtained tubular knit fabric was excellent in anti-see-through properties, moisture absorption properties, and dry feeling, and was at an acceptable level in terms of processability and quality. The results are shown in Table 1.

[0074] Examples 2 to 5, Comparative Examples 1 to 4 The ratio of the discharge amounts of each layer was changed, and the area ratio of the inorganic particle-containing layer and the area ratio of the PEG copolymer-containing layer were changed, but spinning was performed in the same manner as in Example 1 to obtain POY and DTY. The results are shown in Table 1.

[0075] [Table 1]

[0076] Examples 6 to 7, Comparative Examples 5 to 6 Except for changing the content of the inorganic particles, POY was obtained by spinning in the same manner as in Example 1, and DTY was obtained. The results are shown in Table 2.

[0077] Comparative Example 7 Except for changing the area ratio of the inorganic particle-containing layer and the content of the inorganic particles, POY was obtained by spinning in the same manner as in Example 1, and DTY was obtained. The results are shown in Table 2.

[0078] [Table 2]

[0079] Example 8, Comparative Example 8 POY was obtained by spinning in the same manner as in Example 1, except for changing the copolymerization ratio of polyethylene glycol (PEG6000S manufactured by Sanyo Chemical Industries, Ltd.) used as polymer 2, and then DTY was obtained. The results are shown in Table 3.

[0080] Example 9 A three-component conjugate spinning machine was used, and the discharge rate of each component polymer was adjusted using individual extruders, polymer piping and metering pumps, and a concentric three-layer laminated composite cross section was discharged using a composite spinneret utilizing fine flow paths as shown in Figure 1 so that the cross-sectional area ratios of each layer were polymer component 3: 46%, polymer component 1: 24%, and polymer component 2: 20%, respectively. Spinning was performed in the same manner as in Example 1, except that POY and DTY were obtained. The results are shown in Table 3.

[0081] Example 10 A three-component conjugate spinning machine was used, and the discharge rate of each component polymer was adjusted using individual extruders, polymer piping, and metering pumps, and a concentric eight-layer laminated composite cross section was discharged using a composite spinneret utilizing a fine flow path as shown in Figure 1 so that the cross-sectional area ratios of each were polymer component 1:24%, polymer component 2:20%, and polymer component 3:56%, and POY and DTY were obtained by spinning in the same manner as in Example 1. The results are shown in Table 3.

[0082] Example 11 A polyamide (PA-F) containing 50% by mass of rutile-type titanium oxide in nylon 6 with a relative viscosity in sulfuric acid of 2.20 and containing 0.02% by mass of titanium oxide is used as polymer component 1. A polyamide copolymerized with 50% by weight of polyethylene glycol (PEG6000S manufactured by Sanyo Chemical Industries) is used as polymer component 2. A nylon 6 (PA-G) with a relative viscosity in sulfuric acid of 2.60 and containing 1.85% by mass of titanium oxide is used as polymer component 3.

[0083] A three-component composite spinning machine is used, and the extrusion rate of each component polymer is adjusted using individual extruders, polymer piping, and metering pumps. The outermost layer is made of polymer component 3, the two middle layers are made of polymer component 1, the three middle layers are made of polymer component 3, and the fourth middle layer is made of polymer component 2. A concentric four-layer laminated composite cross section as shown in Figure 2 is extruded using a composite spinneret that utilizes fine flow paths as shown in Figure 1 so that the cross-sectional area ratios of each are polymer component 1: 24%, polymer component 2: 20%, and polymer component 3: 56%.

[0084] The yarn discharged from the composite spinneret was cooled and solidified by a yarn cooling device, and then a spinning oil was applied by an oiling device. The yarn was then taken up at a take-up roller speed (spinning speed) of 3000 m / min, stretched at 1.3 times the peripheral speed ratio between the draw rollers, and then wound up at a take-up speed of 3900 m / min to obtain a drawn yarn of 44 dtex-34 filaments (single yarn fineness 1.3 dtex). The thickness of the outermost layer of the drawn yarn was 0.62 μm. The inorganic particle content in the fiber was 12 mass%. The results are shown in Table 3.

[0085] [Table 3] [Explanation of symbols]

[0086] 1: Weighing plate 2:Distribution plate 3: Discharge plate 4: Outermost layer 5: A polymer layer that exists one layer inside the perfect circle that circumscribes the cut surface of the fiber cross section 6: Polymer layer located closer to the center than the perfect circle circumscribing the cut surface of the fiber cross section A: Any point on the circumference of the fiber cross section B: Fiber core C: Fiber radius D: Any point on the circumscribing circle of the polymer layer that is one point inside the perfect circle that circumscribing the cut surface of the fiber cross section E: Fiber radius

Claims

1. In the fiber cross section perpendicular to the fiber axis, It has a multi-layer structure in which three or more types of polymer components are laminated in 3 to 15 layers similar to the fiber surface, The inorganic particles are contained in an amount of 5% by mass to 40% by mass relative to the total amount of the fibers, A multi-layer laminated composite cross-section fiber having a ΔMR of 2.0% or more and 10.0% or less.

2. 2. The multi-layer laminated composite cross-section fiber according to claim 1, wherein one of the three or more polymer components is a moisture-absorbing polymer, and the moisture-absorbing polymer is a PEG copolymer.

3. 2. The multi-layer laminated composite cross-section fiber according to claim 1, wherein the three or more polymer components are all polyesters and have a strength of 2.0 cN / dtex or more.

4. 2. The multi-layer laminated composite cross-section fiber according to claim 1, wherein at least one layer closer to the center of the fiber than the outermost layer of the multi-layered fiber surface contains 30% to 70% by mass of inorganic particles, and a total area ratio of the layers containing the inorganic particles is 10% to 40%.

Citation Information

Patent Citations

  • Conjugate yarn improved in hygroscopicity, blended yarn comprising the same and fabric

    JP1997256224A

  • Sea-islands type composite fiber having excellent moisture absorbability, textured yarn, and fiber structure

    WO2018012318A1